Implications Of Digital Transformation and Cultural Conflict at PT. Bank Amanah Rakyat - Ivon Harnela Wahana; Depit Hariyanto; Herina; Syaiful Bahri; Akhmad Mauliady (Hut Publication Business and Management, 2025)
This research aims to analyze digital transformation and organizational culture at PT. Bank Amanah Rakyat (BAR), as a medium-sized bank with a conservative organizational culture, faces serious challenges in the implementation of the "BAR Digital First" program. Changes that are designed behind closed doors and a lack of communication cause employee resistance in the form of economic fear, group inertia, veiled resistance, and selective perception. This paper aims to analyze change management problems in PT. BAR and formulate the right strategy to manage stakeholders and overcome employee resistance. The analysis method used is an organizational development approach using Force Field Analysis, Kurt Lewin's three-stage change model, resistance to change theory, and stakeholder analysis. The results of the discussion show that the success of digital transformation is highly determined by the psychological readiness of employees, effective communication of change, stakeholder participation, and organizational culture transformation. With the implementation of planned and participatory change management, PT. BAR is expected to be able to increase competitiveness without losing the value of trust that has been built over the years.